2020
DOI: 10.1108/oir-07-2019-0218
|View full text |Cite
|
Sign up to set email alerts
|

Making a higher education institution choice: differences in the susceptibility to online information on students’ advice-seeking behavior

Abstract: PurposeLittle research has been done on how university information sources influence advice-seeking attitude, intention, and behavior between students with high and low susceptibility to online information. Our study addressed this gap by empirically demonstrating the role that students’ susceptibility to online information plays in terms of the effect of attitude, social norm and perceived behavioral control on their advice-seeking intention and behavior using the Theory of Planned Behavior (TPB). The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
9
0
2
Order By: Relevance
“…Given that the study aimed to predict proposed constructs in a research model, PLS-SEM was a suitable choice. Notably, PLS-SEM has been extensively applied to other employability and higher education studies (Santos et al, 2020;Ng et al, 2020Ng et al, , 2021 to perform data analysis. Measurement model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the study aimed to predict proposed constructs in a research model, PLS-SEM was a suitable choice. Notably, PLS-SEM has been extensively applied to other employability and higher education studies (Santos et al, 2020;Ng et al, 2020Ng et al, , 2021 to perform data analysis. Measurement model.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PLS-SEM has been extensively applied to other employability and higher education studies (Santos et al. , 2020; Ng et al. , 2020, 2021) to perform data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Attitudes refer to the degree to which individuals hold favorable or unfavorable evaluations of possible behaviors, as they consider the outcomes of performing certain actions (Fishbein & Ajzen, 1975). This argumentation suggests that individuals are cognizant and knowledgeable on different issues, hence they may be predisposed to hold biased opinions about something or someone (Kim et al, 2020; Ng et al, 2020). In a similar vein, Eagly and Chaiken (1995) contended that the individuals’ attitudes would usually precede their evaluative responses.…”
Section: The Conceptual Framework and The Formulation Of Hypothesesmentioning
confidence: 99%
“…The Theory of Reasoned Action and its related Theory of Planned Behavior were used by different researchers to explore the individuals’ attitudes, perceptions and beliefs toward online information (Kim et al, 2020; Ng et al, 2020; Zimmer et al, 2010). Attitudes refer to the degree to which individuals hold favorable or unfavorable evaluations of possible behaviors, as they consider the outcomes of performing certain actions (Fishbein & Ajzen, 1975).…”
Section: The Conceptual Framework and The Formulation Of Hypothesesmentioning
confidence: 99%
“…This analysis was based on 3 perspectives: technology, pedagogy, and accessibility. Ng et al (2020) examined how the information provided on the Internet influences the choice of HEIs by entrants and investigated the marketing tools of influence through online sources. Máñez-Carvajal et al (2021) found that among the main difficulties that users may face on the sites of HEIs are those related to the perception of information and navigation on the site; another problem is a low level of web-availability on the websites of HEIs of different countries.…”
Section: Literature Reviewmentioning
confidence: 99%